Disability glare: A study in simulated road lighting conditions. (December 2014) - Davoudian, N; Raynham, P; Barrett, E
Disability glare is associated with veiling luminance caused by light from bright sources being scattered within the eyes of observers, thereby reducing retinal luminance contrast. This study compares the reduction in observers' performance in the presence of glare with veiling luminance in the eye, calculated using a non-subjective method. A total of 42 observers performed a target detection task in the presence of a glare source in conditions similar to street lighting at night. Luminance contrast thresholds were measured for each observer under different levels of glare. Results show that, while veiling luminance has a significant effect on the performance of observers, its effect is lower than expected from contrast loss. Furthermore, the performance of observers over the age of 50 is unaffected by increasing the glare level.